Comparative Study of Surgical Outcome of Chronic Subdural Hematoma Treated with and without External Drainage - Sapkota, Suresh; Niraula, Kiran; Lohani, Subash; Shrestha, Shikher; Shrestha, Bibhusan; Shaheen, Ashraf (Eastern Green Neurosurgery, 2020)
Background and purpose: Chronic subdural hematoma (cSDH) poses a significant morbidity and mortality risk particularly in elderly population. It can be treated with simple surgical techniques like burr hole drainage under local anesthesia, however it often recurs after surgical evacuation in significant number of patients.Material and methods: A randomized controlled trial was designed at Mayo Hospital/KEMU in 2013 to 2016. Total number of 98 patients who met the inclusion and exclusion criteria were randomized into ‘with drain’ and ‘without drain’ arm. All of them were treated with burr hole drainage under local anesthesia. Half of them had subdural drain while the remaining half did not. Recurrence of hematoma and surgical outcome was compared.Result: Among 98 patients included in the study(54 males and 44 females) met the inclusion criteria. Mean age of presentation was 63 years ± 12.4 (range 40-100). There was left sided preponderance in hematoma location (53.1%). Mean midline shift was 2.7 mm ± 1.5. Owing to drainage of cSDH, post-operative MRC score of patients along with midline shift in the CT brain showed statistically significant improvement. However, irrespective of insertion of drainage system, there was no significant difference noted in recurrence of cSDH, midline shift and improvement in presenting symptoms (hemiparesis or monoparesis) considering all post-operative days.Conclusion: There is no significant difference in recurrence rate depending on weather a postoperative external drainage is placed or not.